Fungus ball in concha bullosa, an unusual site: a case report from hilly region - ., Shaweta; Minhas, R. S.; Sharma, Vineeta; Verma, Santwana; Guleria, Trilok C. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Fungus is a rare cause of rhinosinusitis in children. Its incidence has been reported as ranging between 13.5 and 28%. Fungus balls are extramucosal tangled masses of fungal hyphae. It commonly involves just one paranasal sinus. Most commonly maxillary sinus is involved and occasionally sphenoid sinus. Concha bullosa is one of the most common anatomical variations in the nasal cavity, with a frequency of reporting ranging from 14-53.6%. There are very few case reports in which Concha bullosa was affected with fungus ball. In this case report 13 years female child presented with complaints of swelling right cheek. The patient underwent endoscopic sinus surgery and there was involvement of concha bullosa and sphenoid sinus with fungus ball. Fungus was confirmed on microscopic examination and culture. Fungus ball is a rare presentation of fungal rhinosinusitis. It should be considered in enlarged middle turbinate with heterogenous opacity on CT. The diagnosis should be confirmed by microscopy or culture.